2019
DOI: 10.1002/ejsp.2560
|View full text |Cite
|
Sign up to set email alerts
|

Women experience more serious relationship problems when male partners endorse hostile sexism

Abstract: Men's hostile sexism promotes aggressive attitudes, motivations and behaviors toward women. Despite the costs these effects should have for women, prior research has failed to test how men's hostile sexism predicts the problems women experience in important domains. We address this oversight by utilizing dyadic data from 363 heterosexual couples to test how male partners’ hostile sexism predicts women's relationship experiences and evaluations. Male partners’ hostile sexism was associated with women experienci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 93 publications
(269 reference statements)
1
17
0
Order By: Relevance
“…Similarly, men who more strongly endorse hostile sexism tend to be less open and self‐protective in relationship‐threatening situations, which ruins the chance to improve problems and instead damages relationships (Overall, Sibley, & Tan, ). Accordingly, men who endorse hostile sexism experience lower relationship satisfaction (Hammond & Overall, ; Sibley & Becker, ) and more serious relationship problems, particularly problems involving power, dependence, and trust (Cross & Overall, ). Thus, resisting partners' influence may help men who endorse hostile sexism feel more independent and protected from the risk of exploitation, but means that they forgo intimacy and growth in their relationships.…”
Section: The Insecurity Within Men's Hostile Sexismmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, men who more strongly endorse hostile sexism tend to be less open and self‐protective in relationship‐threatening situations, which ruins the chance to improve problems and instead damages relationships (Overall, Sibley, & Tan, ). Accordingly, men who endorse hostile sexism experience lower relationship satisfaction (Hammond & Overall, ; Sibley & Becker, ) and more serious relationship problems, particularly problems involving power, dependence, and trust (Cross & Overall, ). Thus, resisting partners' influence may help men who endorse hostile sexism feel more independent and protected from the risk of exploitation, but means that they forgo intimacy and growth in their relationships.…”
Section: The Insecurity Within Men's Hostile Sexismmentioning
confidence: 99%
“…Another key implication of our perspective that (in)security is central to understanding sexism is that the resulting relationship dynamics likely generate self‐fulfilling cycles that reinforce people's endorsement or rejection of sexist attitudes. For instance, the relationship aggression arising from men's hostile sexism produces hostility, dissatisfaction, and lower commitment in female partners (Cross & Overall, ; Overall et al, ), and these partner reactions likely affirm men's beliefs that women cannot be trusted. Conversely, relationship conditions that offer security can attenuate the aggression associated with men's hostile sexism (Cross et al, ; also see Sheppard & Johnson, ), and perhaps will reduce hostile sexism across time.…”
Section: Theoretical Advancements and Future Directionsmentioning
confidence: 99%
“…Collecting information from the other dyad member would allow identification of mutual aggressions (Low, Tiberio, Shortt, Capaldi, & Eddy, 2016) and to explore the role that hostile sexism plays in this process. Examining psychological aggression by the participant's partner, and the impact this aggression has, also will clarify whether the psychological aggression assessed in the current study represents violence victimization as experienced by intimate partners (Cross & Overall, 2018) and allows us to identify the existence of either psychological damage or malingering (Arce, Fariña, & Vilariño, 2015;Vilariño, Amado, Vázquez, & Arce, 2018).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…For instance, hostile sexism predicts greater acceptance of gender income inequality and more negative perceptions of female breadwinners than of women portrayed in traditional roles (Connor & Fiske, 2019; Gaunt, 2013). Other research suggests that hostile sexist attitudes hinder women’s autonomy by being associated with perceptions that men have the right to constrain women’s reproductive choices (Patey et al, 2019; Petterson & Sutton, 2018) and maternal behaviors (Huang et al, 2020) Men who more strongly endorse hostile sexism are reported to be more physically and verbally aggressive toward their partners (e.g., Forbes et al, 2004; Martinez-Pecino & Durán, 2019) and women experience more severe problems in their relationship when their partners more strongly endorse hostile sexism, including jealousy, gender-role conflict, abuse, affairs and addiction (Cross & Overall, 2019). Considering these significant costs for women, the absence of a link between men’s hostile sexism and women’s relationship adjustment in our study is puzzling.…”
Section: Discussionmentioning
confidence: 99%